Medical complications during inpatient rehabilitation in patients with ischemic stroke in a tertiary care hospital in Nepal - Dhungana, Krishna; Shakya, Dipesh; Shrestha, Rabindra; Bhatta, Sabnam; Maharjan, Sabbu (Journal of Kathmandu Medical College, 2020)
Background: Complications are common in patients with ischemic stroke and hinder successful rehabilitation. Timely identification and management of complications are key factors in the management of patients with ischemic stroke. Objectives: The aim of this study is to find the occurrence of different types of complications in patients admitted with the diagnosis of ischemic stroke and to find the risk factors associated with the occurrence of complications. Methodology: The study is a cross sectional descriptive study. A total of 96 patients with ischemic stroke admitted to the Department of Neurology of Kathmandu Medical College Teaching Hospital over a period of six months (July 2018 to December 2018) were recruited. Data was recorded according to a designed proforma and analysed using Statistical Package for the Social Sciences version 20. Results: The age group ranged from 25 to 91 years with the mean age of 64.36 years and 50 (52.1%)patients were male. A total of 62 (64.6%) patients developed at least one complication during hospital stay. Pneumonia and urinary tract infection were the most common complications occurring in 22(22.9%) patients. The occurrence of complications was positively correlated with National Institutes of Health Stroke Scale and Glasgow Coma Scale. Conclusion: Pneumonia and urinary tract infection were the most common complications in our study and were similar to those quoted in the western literature. Severity of stroke had positive correlations with occurrence of complications.